Persepsi Guru-Guru Sekolah Agama Rakyat Tentang Kurikulum Dan Pengajaran - Jusoh, Ismail (Penerbit Universiti Sains Malaysia, 2000)
This article elaborates the results of a case study on perceptions of religious school teachers on curriculum and teaching. The study was conducted based on the concepts introduced by Prof. Or. Abdullah Nasih Ulwan (1988) who claimed that there were two schools of thoughts that influence the school teachers perceptions.